Peranan Lingkungan Sosial terhadap Pembentukan Karakter Peduli Lingkungan Mahasiswa Pendidikan Geografi di Universitas Samudra Langsa - Fitria Mustika; Tengku Muhammad Sahudra (Universitas Negeri Medan, 2018)
This study aims to determine the role of the family, community, and tertiary environment towards the formation of caring character in the geography education student environment. The output of this study was a four-indexed indexed education journal and a UNIMED google scolar. Samples from the study population were 20 respondents with 30 items about questionnaires. The time of the study starts from May 2018 to October 2018. The measurement scale in this study is the scale of the briquette. Data collection by means of library studies, interviews, questionnaires, and documentation. This research was conducted by distributing questionnaire questionnaires and interviews. Based on the results of questionnaire data processing, the family environment has a very high frequency in the formation of character of the student's environmental care with an achievement level of a total score of 91%. Furthermore, the role of the campus environment also has a high frequency in the formation of the character of the student's environmental care with a total score of 89%. Whereas the family environment has a low frequency in the formation of character of student environmental care with a total score of 57%. It can be concluded that the family environment has the most role in forming the character of the student's environmental care.